Gender Justice Discourse in the Educational System of Afghanistan during the Democracy Period (2001 – 2015) - Sokhanwar, Davood (European Journal of Social Science Education and Research, 2019)
This study seeks to examine Afghan women’s access to education (gender justice) in the wake of September 11 amid developments and efforts made to establish democracy in this country in the years between 2001 and 2014. Using discourse analysis, this research aims to extract one nodal point and several floating signifiers to explore a semantic system of gender justice, albeit by making use of examples taken from the educational system during the mentioned period. The data collected in this research are extracted from texts concerning the role of women in education in Afghanistan in the mentioned period. Its importance in terms understanding the intellectual and political atmosphere of the mentioned political system especially in respect of women’s access to their educational rights is brought to light. This study concludes that the gender equality index is satisfactory to a great deal in the present government as compared to the period of Taliban in which the index was lowest in the world. However, the present government has not achieved success as much as it was expected because gender justice discourse has not become hegemonic in Afghanistan. The reason for the unsuccessfulness of the discourse lies in the elements that make the discourse hegemonic. Because elements could not play their effective role, this discourse did not become hegemonic.